Simulating the Effects of Policy Interventions on Socio-Economic Development: Case Studies and Methodologies - Verma, Shubhi; Tiwari, Ankit (International Journal of Technology and Modeling, 2024)
This study explores the impact of policy interventions on socio-economic development through simulation-based methodologies, focusing on selected case studies in India. Utilizing systems dynamics modeling and agent-based simulations, the research examines how targeted policies in sectors such as education, healthcare, and rural infrastructure influence economic growth, income distribution, and social mobility over time. The case studies include region-specific implementations, allowing for a nuanced understanding of policy effectiveness in diverse socio-economic contexts. Results highlight the interplay between policy design, regional characteristics, and long-term developmental outcomes. The findings offer actionable insights for policymakers aiming to optimize intervention strategies, reduce inequalities, and foster inclusive growth. Methodologically, this paper contributes a comparative framework for simulating policy scenarios, which can be adapted and applied to other developing country contexts.